Digital Models as an Alternative to Plaster Casts in Assessment of Orthodontic Treatment Outcomes. (12th June 2018) - Leung, Chung-Yan Vanessa; Yang, Yanqi; Liao, Chongshan; Hägg, Urban; Wong, Ricky Wing Kit; McGrath, Colman; Gu, Min
Abstract : Objective . This study aimed to compare the use of digital models and plaster casts in assessing the improvement in occlusion following orthodontic treatment. Materials and Methods . Digital models and plaster casts of 39 consecutive patients at pre- and posttreatment stages were obtained and assessed using the Peer Assessment Rating (PAR) index and the Index of Complexity and Treatment Need (ICON). PAR and ICON scores were compared at individual and group levels. Categorization of improvement level was compared using Kappa (κ ) statistics. Results . There was no significant difference in neither PAR scores ( p > 0.05) nor ICON scores ( p > 0.05) between digital and plaster cast assessments. The Intraclass Correlation Coefficient (ICC) values for changes in PAR and ICON scores were excellent (ICC > 0.80). Agreement of ratings of occlusal improvement level between digital and plaster model assessments was 0.83 (κ ) for PAR and 0.59 (κ ) for ICON, respectively. Conclusion . The study supported the use of digital models as an alternative to plaster casts when assessing changes in occlusion at the 'individual patient' level using ICON or PAR. However, it could not fully support digital models as an alternate to plaster casts at 'the group level' (as in the case of clinical audit/research).